A Detailed Structural Review of Onshore and Offshore Pipelines Containing Defects - Ebili, Frederick; Oterkus, Selda; Oterkus, Erkan (Sustainable Marine Structures, 2025)
This study presents a thorough and holistic review of various studies focusing on the structural analysis of Oil and Gas (O&G) pipelines, with an emphasis on various defect modes. The study appraised pipeline-related articles from the empirical, semi-empirical, analytical, and numerical studies. However, the study's core objective remains to address the persistent challenge that often leads to Burst Pressure Loss (BPL) in a pipeline. These mechanical-associated damages, which can result in BPL, may include pipe scratches, dents, or cracks. Therefore, training a large volume of datasets in neural network architectures or the finite element domain is crucial in this context. The study further explores previous research to gain a deeper insight into how many modes of damage enhance loss in Burst Pressure (BP). The study further synthesises significant reasons why pipeline Structural Health Failures (SHFs) occur, as drawn from existing literature. Failure scenarios in pipeline dent, crack, fracture, buckling, fatigue, corrosion, BPL, and Third-Party Damage (TPD) could result from mechanical deformation, ageing, insufficient real-time monitoring, and TPD influences. Many of the assessed articles conclude that the experimental approach and Finite Element Method (FEM) are valid and can accurately validate one another in the analysis and prediction of pipeline failures. However, this study offers valuable and comprehensive resources for pipeline engineers, academic researchers, and industry professionals. Again, the study is crucial for pipeline fabricators, installers, and operators to keep up with maintenance, repairs, and predictions. ER